2011
DOI: 10.1002/app.33884
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Amidoximation of Polyacrylonitrile Films: Influence of Synthesis Conditions

Abstract: Chemical transformation of acrylic membranes with hydroxylamine hydrochloride (HA) was carried out to introduce amidoxime groups. It was found that the reaction conditions, such as reaction time, HA concentration and temperature influence the amidoxime content, significantly. A sharp enhancement in the amidoximation at 80 C was observed. The FTIR studies showed a significant loss of nitrile groups during amidoximation process. Optimum conditions for the amidoximation process were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…1, raw PAN showed characteristic peaks related to -C^N stretching vibration at $2242 cm À1 , -C^N bending vibration at $1070 cm À1 , -CH stretching vibration at $2935 cm À1 , and -CH 2 stretching vibration at $1452 cm À1 . 23,29,32 The gradual decrease of -C^N peak intensities together with the appears of N-O ($913 cm À1 ), N-H ($3368 cm À1 ) and O-H ($3336 cm À1 ) 19,31,32 aer the amidoximation reaction revealed the successful conversion of PAN into PAO. The N-O, N-H and O-H vibrations appeared, increased, and decreased with the performance of the amidoximation reaction.…”
Section: Effect Of Amidoximation Time and Temperature On Surface Property Of Paomentioning
confidence: 96%
See 1 more Smart Citation
“…1, raw PAN showed characteristic peaks related to -C^N stretching vibration at $2242 cm À1 , -C^N bending vibration at $1070 cm À1 , -CH stretching vibration at $2935 cm À1 , and -CH 2 stretching vibration at $1452 cm À1 . 23,29,32 The gradual decrease of -C^N peak intensities together with the appears of N-O ($913 cm À1 ), N-H ($3368 cm À1 ) and O-H ($3336 cm À1 ) 19,31,32 aer the amidoximation reaction revealed the successful conversion of PAN into PAO. The N-O, N-H and O-H vibrations appeared, increased, and decreased with the performance of the amidoximation reaction.…”
Section: Effect Of Amidoximation Time and Temperature On Surface Property Of Paomentioning
confidence: 96%
“…The conversion of PAN to PAO is fairly dependent on amidoximation conditions (such as amidoximation time, temperature and NH 2 OH concentration). 9,[17][18][19][20][21][22][23] High temperature, high NH 2 OH concentration and a long reaction time benet the diffusion of NH 2 OH from solution into the PAN matrix and enhance PAN conversion and H 2 L I formation. 13,14,21 However, because of the instability of PAO, unproper amidoximation conditions result in the degradation and decomposition of PAO.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of hydroxylamine with nitrile group, affords amidoxime functionality 5 and this kind of modification was mainly carried out on PAN surface (Scheme ). The influence of reaction conditions on amidoximation of PAN films was studied by Gupta and coworkers and observed that, the reaction conditions, such as reaction time, hydroxyl amine concentration, and temperature certainly influence the amidoxime formation. Hydroxyl amine has also been used together with other nucleophiles for the nitrile modification reaction targeting improved properties.…”
Section: Nitrile Group Modifications In Polymersmentioning
confidence: 99%
“…Hydroxylamine hydrochloride has been widely used as a reducing agent in various resins including PAN by converting the nitrile groups into AO groups [1,10,31]. In this study, the refined methods (convenient and economic methods) for the modification of poly(AN-co-AA) system have been achieved by altering some of the methodologies from a previous literature review ( Table 1).…”
Section: Amidoxime (Ao) Modified Poly(an-co-aa)mentioning
confidence: 99%
“…For instance, poly(AN-co-AA) has a better affinity for water due to the existence of -COOH pendant groups contributed by acrylic acid constituent along the polymer chains. In contrast, PAN was known as a hydrophobic polymer due the nitrile-nitrile dipolar interactions along PAN chains [1,3]. Hence, it is expected that the AO modified poly(AN-co-AA) 93:7 has high potential to make efficient adsorptions in aqueous solution and waste water.…”
Section: +mentioning
confidence: 99%